Patient Satisfaction, Hospital Image and Patient Loyalty in West Sulawesi Province - Abdul Haeba Ramli (Business and Entrepreneurial Review, 2017)
The purpose of this study was to examine and analyze the effect of patient satisfaction and hospital image on patient loyalty. The research design uses a survey method with cross-section data collection through a questionnaire. As a sample in this study, 124 patients were hospitalized at a Private Hospital located in West Sulawesi Province and taken by simple random sampling. The data analysis method used in hypothesis testing is Structural Equation Modeling (SEM). The results of the study provide evidence that patient satisfaction affects and can improve the image of the hospital. High patient satisfaction also has an impact on patient loyalty, as well as the high Sakityang house image has a positive and significant influence on patient loyalty.